1976
DOI: 10.1017/s0007114500020158
|View full text |Cite
|
Sign up to set email alerts
|

The B-vitamins in malnutrition with alcoholism: A model of intervitamin relationships

Abstract: 1. The B-vitamin status of fifty-nine patients, mainly from the lower socio-economic classes in Bombay, with a history of chronic malnutrition, and of alcoholism of 1·5–20 years’ duration, was studied before and during treatment, and in relation to their clinical, especially neurological, condition. These patients were divided into two neurological categories: (1) those with peripheral neuropathy (mainly sensory and distal) alone, (2) those with mental changes (mainly confusion and disorientation) also. Both c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Numerous studies have demonstrated that chronic alcohol consumption leads to B vitamin deficiency [36,37]. Compared with the control group, the myocardial tissue of mice in the ACM group exhibited decreased levels of several B vitamins, including thiamine (vitamin B1), riboflavin (vitamin B2), pantothenic acid (vitamin B5), and nicotinamide (the metabolite of niacin, vitamin B3).…”
Section: Metabolism Of B Vitaminsmentioning
confidence: 99%
“…Numerous studies have demonstrated that chronic alcohol consumption leads to B vitamin deficiency [36,37]. Compared with the control group, the myocardial tissue of mice in the ACM group exhibited decreased levels of several B vitamins, including thiamine (vitamin B1), riboflavin (vitamin B2), pantothenic acid (vitamin B5), and nicotinamide (the metabolite of niacin, vitamin B3).…”
Section: Metabolism Of B Vitaminsmentioning
confidence: 99%
“…Increased dietary intake of niacin (nicotinic acid) has been associated with improved cognitive performance ( 5 ) and reduced risk of age-associated cognitive decline and AD ( 6 ). Niacin is obtained principally through diet and is able to cross the blood-brain barrier ( 7 ), as evidenced by its detection in the mouse brain and human cerebrospinal fluid ( 8 , 9 ). Thus, we postulated that the actions of niacin within the brain may be of therapeutic utility for AD.…”
Section: Introductionmentioning
confidence: 99%
“…However, this reaction requires an acidic pH and millimolar concentrations of nicotinic acid. These requirements will hardly be met in vivo [7,8]. CD38 is a multifunctional enzyme which in addition catalyses the hydrolysis of NAD to ADPR, and to a minor extent also to cADPR [9], and the degradation of NAADP [10].…”
Section: Introductionmentioning
confidence: 99%